Influence of Paclobutrazol and Ethephon on Vegetative Growth of Guava (Psidium guajava L.) Plants at Different Spacing - Jaswinder Singh BRAR (Notulae Scientia Biologicae, 2010)
To ascertain the growth retarding potential of Paclobutrazol (PBZ) and Ethephon on guava plants at different spacing viz 62 m, 63 m, 64 m and 65 m; both were applied at 500 ppm, 1000 ppm as a foliar spray. Investigation revealed that all treatments influence the vegetative growth of plants compared to untreated plants at all spacing levels. However, paclobutrazol considerably restrict the overall vegetative growth of trees. Stock and scion girth was found to be increased with ethephon treatments. The tree height and E-W tree spread was found to increased with increasing plant density. Similarly, trunk girth in terms of stock and scion girth was also increased with increase in plant spacing. Although, the PBZ 500 ppm markedly restrict the plant growth but it may be further investigated for managing the guava tree canopies under high density planting systems, taking the fruit quality and economic aspects into consideration.